2014
DOI: 10.3390/vaccines2020196
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Molecular Adjuvants Expressing NF-Kappa B Subunit p65/RelA or Type-1 Transactivator T-bet Enhance Antigen Specific DNA Vaccine-Induced Immunity

Abstract: DNA vaccine-induced immunity can be enhanced by the co-delivery of synthetic gene-encoding molecular adjuvants. Many of these adjuvants have included cytokines, chemokines or co-stimulatory molecules that have been demonstrated to enhance vaccine-induced immunity by increasing the magnitude or type of immune responses and/or protective efficacy. In this way, through the use of adjuvants, immune responses can be highly customizable and functionally tailored for optimal efficacy against pathogen specific (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…This is very important in a disease such as prostate cancer where symptoms from the disease are generally not present until the late stages (14). However, many studies have indicated that a vaccine containing only an antigen is not effective enough to induce an anti-tumor immune response (4,15). …”
Section: Discussionmentioning
confidence: 99%
“…This is very important in a disease such as prostate cancer where symptoms from the disease are generally not present until the late stages (14). However, many studies have indicated that a vaccine containing only an antigen is not effective enough to induce an anti-tumor immune response (4,15). …”
Section: Discussionmentioning
confidence: 99%
“…Examples of adjuvants [19][20][21][22][144][145][146]. reported nanoparticles of chitosan combined with tripolyphosphate and hemagglutinin (HA) induced a two-fold increase in the number of splenocytes that secrete IFNc in mice infected with the influenza virus when compared with a nonadjuvanted HA vaccine [20].…”
Section: Tablementioning
confidence: 99%
“…Kalams, et al also evaluated the positive impact of EP delivery methods for the HIV-1 Gag antigen/IL-12 adjuvant plasmid vector in a phase I clinical trial. Other studies have also assessed the immunogenicity of DNA vaccines containing chemokine-expressing sequences for HIV-1 immunization [144][145][146]. The CpG oligodeoxynucleotide (ODN) is another common genetic adjuvant used for DNA vaccines [9,147,148].…”
Section: Techniques To Overcome Immunogenic Issues Of Dna Vaccinesmentioning
confidence: 99%
“…NF-κB is a master innate immune regulator. A recent study showed that co-administration of a plasmid expressing NF-κB subunit p65/ RelA enhanced DNA vaccine immunogenicity [107]. A T-cell transcription factor, Tbet was effective in driving a Th1 response against an Ag85B DNA-based tuberculosis vaccine [108,109].…”
Section: Plasmid-encoded Signalling Moleculesmentioning
confidence: 99%